2018
DOI: 10.3389/fmicb.2018.01299
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy to Control Clinically Relevant Biofilm Infections

Abstract: Biofilm describes a microbially-derived sessile community in which microbial cells are firmly attached to the substratum and embedded in extracellular polymeric matrix. Microbial biofilms account for up to 80% of all bacterial and fungal infections in humans. Biofilm-associated pathogens are particularly resistant to antibiotic treatment, and thus novel antibiofilm approaches needed to be developed. Antimicrobial Photodynamic therapy (aPDT) had been recently proposed to combat clinically relevant biofilms such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
264
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(278 citation statements)
references
References 250 publications
(273 reference statements)
4
264
0
10
Order By: Relevance
“…The inappropriate prescription of antimicrobials or their overuse exacerbates the problem [ 3 ]. The formation of biofilms is also responsible for an increase in the level of microbial resistance [ 4 ]. In fact, several microorganisms, such as bacteria, fungi, green algae, cyanobacteria, and lichen, possess the ability to grow in biofilm form and they are usually incorporated in a matrix of extracellular polymeric substances (EPS) auto-produced by the microorganisms, which makes the penetration of antimicrobial drugs difficult [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inappropriate prescription of antimicrobials or their overuse exacerbates the problem [ 3 ]. The formation of biofilms is also responsible for an increase in the level of microbial resistance [ 4 ]. In fact, several microorganisms, such as bacteria, fungi, green algae, cyanobacteria, and lichen, possess the ability to grow in biofilm form and they are usually incorporated in a matrix of extracellular polymeric substances (EPS) auto-produced by the microorganisms, which makes the penetration of antimicrobial drugs difficult [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic inactivation (PDI) is an antimicrobial strategy that has been reported as an effective method to inactivate a broad spectrum of pathogens [ 12 , 13 , 14 ], including microorganisms that are highly resistant to conventional antimicrobials [ 15 ] and those that form biofilms [ 4 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The control and reduction of oral biofilm formation [1], initiated by bacterial species living in polymicrobial, pathogenic colonies at or below the gingival margin [2], are critical steps toward the prevention of dental caries and periodontal diseases [3][4][5]. While many methods have been proposed to prevent or treat these biofilms [6][7][8][9][10], one promising strategy is the use of synthetic polymer additives that bind to the tooth surface to act as a barrier or deterrent to the deposition of planktonic bacteria through either lethal [11][12][13] or non-lethal [14,15] mechanisms. Dental materials, especially those delivered from common over the counter products such as toothpaste or mouthwash, must effectively be multifunctional materials in that they must (1) deposit and stick to a tooth surface, (2) act as a barrier against bacteria attachment, (3) be robust against external challenges such as food and drink in order to not require constant reapplication, and (4) perform steps 1-3 in the presence of the salivary pellicle.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally reported that Gram‐positive microorganisms are more sensitive to antimicrobial agents as compared to Gram‐negative ones. Gram‐positive microbes (S. aureus) have thick cell wall (Hu, Huang, Wang, Wang, & Hamblin, ) than Gram‐negative cells ( E. coli ) which can increase the interaction between the garlic active compounds and the structural components. Moreover, cell membrane of Gram‐negative bacteria blocks the penetration of the active compounds which make them resistant.…”
Section: Resultsmentioning
confidence: 99%